2021
DOI: 10.1002/acm2.13266
|View full text |Cite
|
Sign up to set email alerts
|

EUS‐guided hydrogel microparticle injection in a cadaveric model

Abstract: Background and Aims A potential method to reduce gastrointestinal toxicity during radiation therapy in pancreatic head cancer is to create a physical space between the head of the pancreas (HOP) and the duodenum. To date, there have been early reports on the feasibility of endoscopic ultrasound (EUS)‐guided hydrogel injection into the interface between the HOP and the duodenum to increase the peri‐pancreatic space for radiotherapy. We aimed to evaluate the technical feasibility of EUS‐guided hydrogel injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Our group has shown that injection of hydrogel spacer between the head of pancreas (HOP) and duodenum increases the duodenal sparing, and therefore, makes the dose escalation more feasible. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, the success of the spacer placement procedure is highly uncertain. Previous studies on rectal spacer have shown that hydrogel spacer injection is associated with risk of infection, inflammation, and softtissue wall infiltration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has shown that injection of hydrogel spacer between the head of pancreas (HOP) and duodenum increases the duodenal sparing, and therefore, makes the dose escalation more feasible. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, the success of the spacer placement procedure is highly uncertain. Previous studies on rectal spacer have shown that hydrogel spacer injection is associated with risk of infection, inflammation, and softtissue wall infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of dose escalation is limited due to the proximity of organs at risk (OAR), mainly the duodenum. Our group has shown that injection of hydrogel spacer between the head of pancreas (HOP) and duodenum increases the duodenal sparing, and therefore, makes the dose escalation more feasible 3–17 …”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 Recent studies have shown that hydrogel spacer resulted in a significant reduction of rectal dose during PT. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 However, the standard rectal hydrogel spacer is not visible on planning computed tomography (CT) and intraoperative cone‐beam CT that lack the adequate resolution and contrast to distinguish between the soft tissue (prostate and rectum) and hydrogel. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Thus, magnetic resonance imaging (MRI) is required to localize the hydrogel spacer, but anatomical changes, patient intolerance, MRI‐incompatible hardware, and the extra cost and time raise the need for an alternative spacer localization method.…”
Section: Introductionmentioning
confidence: 99%
“…Respiration). However, this larger margin will result in delivering greater radiation doses to the area around the tumor, thereby inherently causing toxicities to normal tissues (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). In this case, it is not possible to apply dose escalation without margin reduction (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%